Anomalous Hall Effect and Magnetoresistance in Sputter‐Deposited Magnetic Weyl Semimetal Co2TiGe Thin Films. Issue 1 (10th July 2020) - Dyck, Denis; Becker, Andreas; Koo, Jungwoo; Matalla-Wagner, Tristan; Krieft, Jan; Reiss, Günter
Abstract : Herein, sputter‐deposited ferromagnetic Weyl semimetal (WSM) and full‐Heusler compound Co2 TiGe is investigated. Crystal quality is analyzed using X‐ray diffraction and reflectivity. In addition, temperature‐dependent transport and magnetization measurements are carried out. The sample shows indications on the formation of L21 crystal structure. Magnetization measurements show a saturation magnetization of 1.98 μB (f.u.) −1 and 1.45 μB (f.u.) −1 at 50 and 300 K, respectively. This is in close agreement to the calculated value of 2 μB (f.u.) −1 at 0 K using the Slater–Pauling rule. The obtained Curie temperature is 378.5 K, which is close to prior results for bulk samples. The residual resistivity of 142.7 μΩ cm is mainly dominated by disorder scattering. At temperatures above 60 K, the Coulomb interaction dominates the resistance. The residual resistance ratio is around 1.49. Hall measurements show positive ordinary Hall and anomalous Hall constants and a positive dependence on temperature. Skew scattering and side jumps or intrinsic mechanisms contribute in similar amounts to the anomalous Hall resistivity, which indicates a higher than usual intrinsic contribution, which is expected for WSMs. The expected relation between the longitudinal and the anomalous Hall conductivity of σ xy A ∝ σ xx 0 is not met. Abstract : The physical properties of sputter‐deposited films of the Weyl semimetal (WSM) candidate Co2 TiGe are analyzed. The magnetic as well as the transport properties are comparable with those of bulk samples and confirm a high crystalline quality of the sample. The anomalous Hall effect shows a higher contribution from intrinsic mechanisms, which is expected for WSMs.